The importance of digital skills for the Western Balkans -comparative analysis between the Western Balkans and the European Union - Levkov, Nikola; Kitanovikj, Bojan (Ss. Cyril and Methodius University in Skopje, Faculty of Economics-Skopje, 2024)
In knowledge-intensive economies, skills emerged as crucial resources, determining economic development. Thus, in the post-pandemic, digital world, digital skills gain new ground, attracting the interest of researchers and practitioners, especially in the Western Balkan (WB) countries, which aspire to be a part of the European Union (EU). As a result, the article aims to investigate the level of digital, computer, and skills in evaluating data, information, and digital content in WB and to compare it with the EU region. Furthermore, we found that EU countries are way ahead in terms of basic or above basic overall digital skills on average. In the WB context, Serbia and Montenegro are close to converging with the EU average related to computer skills while Montenegro and North Macedonia lead in skills in evaluating data, information, and digital content. The results point out that the level of digital skills highly correlates with labor productivity and GDP per capita in WB.